STRUKTUR KOMUNITAS IKAN DI PERAIRAN SUNGAI MENDO KABUPATEN BANGKA - ruzul bai niyah; Kurniawan Salim; Eva Utami (Akuatik: Jurnal Sumberdaya Perairan, 2020)
The Mendo River utilizes the local community for washing and bathing (MCK), rice fields, tin mining and fisheries. Sngai Mendo is included in a large river basin (DAS) so that it has the potential for various freshwater fisheries. The research objective was to analyze the diversity of fish found in the Mendo River, Bangka Regency. The research was conducted in February 2020 on the Mendo River. This study used a purposive sampling method at 3 Mendo River stations. The fishing gear used for sampling fish is the trap and net fishing gear (gillnet). The results showed that 9 species were found in the Mendo River, namely Baung (Mystus nemurus), Betok fish (Anabas testudineus), Cork fish (Channa striata), Kelincah fish (Belontia hasselti), Kepatung fish (Pristolepis grotii), catfish (Clarias sp.), Seluang fish (Rasboraca epholotaenia), Sepat fish (Trichogaster trichopterus) and giant prawns (Macrobrachium rosenbergii). The structure of the fish community in the Mendo River is still within the criteria of moderate diversity, which means that their habitat is in optimal condition and in accordance with the biota. The diversity index value of fish using traps ranged from 1.41 to 1.91 while the index value of fish diversity using gillnet fishing gear ranged from 0.61 to 1.31.